Oxidative Stability of Phytosterols in Camellia Seed Oil During Heating: The Impact of Different Antioxidants - Dongkun Zhao; Xin Wang; Sicong You; Lijuan Wang; Usman Amjad; Baocheng Xu; Xinjing Dou; Lili Liu (Foods, 2025)
Phytosterols (PS) have specific oxidation rules in different lipid media. After oxidation, PS will form oxidation products, which has potential physiological toxicity to the human body. Camellia seed oil (CSO) is a unique emerging edible oil in China. This oil has a fatty acid composition similar to olive oil, in which oleic acid is dominant. In order to solve the thermal oxidation of PS in CSO at high temperature (180 °C), we studied its antioxidant strategy by evaluating different antioxidants. Four antioxidants—BHA, TBHQ, epigallocatechin gallate (EGCG), and α-tocopherol (VE)—along with one synergist, citric acid (CA), were selected and used in this study. The antioxidant effects of different combinations (single antioxidant, single antioxidant + CA, mixed antioxidant, mixed antioxidant + CA) were compared. After 180 min of heating, the PS and phytosterols oxidation products (7α-hydroxy-, 7β-hydroxy-, 5α,6α-epoxy-, 5β,6β-epoxy-, 7-keto-, and trihydroxy-PS) were estimated by GC-MS. Through comparative analysis, the results showed that the combination of mixed antioxidants and CA had the best antioxidant effect, and the inhibition rate of VE + TBHQ +CA was as high as 42%, which had a breakthrough significance for stabilizing the thermal oxidation of PS in camellia seed oil. At the same time, it also provides a valuable reference for ensuring the edible safety of camellia seed oil in Chinese food heating habits.